2004
DOI: 10.1017/cbo9780511756207
|View full text |Cite
|
Sign up to set email alerts
|

The 2000 Presidential Election and the Foundations of Party Politics

Abstract: The 2000 Presidential Election presumptive victor to fighting for his political life. In the third phase, he called up memories of the New Deal and succeeded in persuading a critical bloc of voters that George W. Bush was a threat to the Social Security system. In the byplay, however, Gore ignored the robust economy, which should have carried him to a comfortable victory. Still, his playing the New Deal card enabled him to win the popular vote. But he lost the Electoral College and, with it, the election. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
154
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(158 citation statements)
references
References 73 publications
4
154
0
Order By: Relevance
“…In one study, Johnston, Hagen, and Jamieson (2004) aggregate advertisements by blocks as short as five days, a procedure that implies, but does not prove, substantial decay of effects. But in another study, Huber and Arceneaux (2007) aggregate advertisements over a 30-day period, and in still another, Franz and Ridout (2010) aggregate ads in blocks of one, two, and multiple months.…”
Section: Field Studies Of Political Persuasionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, Johnston, Hagen, and Jamieson (2004) aggregate advertisements by blocks as short as five days, a procedure that implies, but does not prove, substantial decay of effects. But in another study, Huber and Arceneaux (2007) aggregate advertisements over a 30-day period, and in still another, Franz and Ridout (2010) aggregate ads in blocks of one, two, and multiple months.…”
Section: Field Studies Of Political Persuasionmentioning
confidence: 99%
“…In their study of the 2000 election, Johnston, Hagen, and Jamieson (2004) found that that Bush's come-from-behind win over Gore was due to a slim advertising advantage in battleground states during the last week. Here we seek to corroborate that finding.…”
Section: Significance Of Findings For Political Campaignsmentioning
confidence: 99%
“…Revisionist accounts, while acknowledging that most citizens fall short of the democratic ideal, still presume some minimal level of exposure to political information. The question of just how much exposure occurs is relevant to a wide range of scholarship exploring everything from the impact of campaigns on voters' level of knowledge about the candidates (see, for example, Craig, Kane, and Gainous 2005;Druckman 2005) to the effects of campaign messages on voter preference (Hillygus and Jackman 2003;Johnston, Hagen, and Jamieson 2004). In general, the question of individual variability in exposure to information is fundamental to political communication research.…”
mentioning
confidence: 99%
“…And CMAG estimates only the cost of the television airtime; the estimates do not include the cost of producing an ad to be aired. has used CMAG data extensively in his work on the effects of campaigns in presidential elections (Johnston et al 2004;Hagen and Johnston 2007). We decided to pool our experience and expand the CSED study protocol to collect station records from all the high-level competitive races in the Philadelphia media market in 2006.…”
Section: Collecting Station Records: Philadelphia 2006mentioning
confidence: 99%
“…Academic studies of campaign effects have deployed CMAG data on the incidence of campaign ads to characterize the advertising to which the electorate has been exposed (Freedman and Goldstein 1999;Goldstein and Freedman 2000, 2002b, 2002aFreedman et al 2004;Johnston et al 2004;Brader 2005Brader , 2006Hagen and Johnston 2007;Franz et al 2007) and to investigate campaign strategy (Goldstein and Strach 2003). CMAG also produces estimates of the cost of ads, which can be aggregated to produce estimates of the total amount spent on television airtime in and across races.…”
mentioning
confidence: 99%